(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Human enhancement is slowly penetrating the legal discourse. A conventional approach frames the problem in terms of fundamental rights and values, or assess its acceptability within a pure cost-benefit analysis. However, we can analyse the attempts at transforming the human body and augmenting mental capabilities from a different angle. The current availability of devices and substances that point to increase physical and cognitive abilities requires exploring the regulatory schemes that shape the relevant markets, with special regard to the safety legislation concerning consumer goods, medical devices and pharmaceuticals, as well as the laws affecting the advertising and selling practices of such products.